Struggle for power among factions a case study of environmental regulations concerning Barbecue Park, Iloilo City, 2011. - Sorongon, Christian D. (2012.)
It is always suspected that politicians would always to actions which are politically motivated particularly based on their respective interest. However, they would usually justify such political acts legally or they use legal instruments in order to pursue political motives. ?The language is legal but the act is political? is an encompassing line for these situations. This research was able to unveil the political factors that resulted to the demolition of Barbecue Park Restaurant owned by Councilor Edward Yee of Iloilo City. It was significantly identified that the political factors were cloaked by a legal framework. The legal framework of the case was also identified and described to serve as a pre-requisite of a preparatory discussion in understanding the political variables that played a role in the said demolition. The political actors and factions and their engagements were identified in this research. Mayor Jed Patrick Mabilog and Congressman Jerry Trenas both of Iloilo City along with Councilor Edward Yee and Senator Franklin Drilon were the main political actors in the case. These four main actors with minor and supporting actors formed factions whether favouring the demolition or not. One significant finding in this research is that there was a re-configuration of the composition of political factions. Notably, Senator Franklin Drilon was identified to be the Big Man of the demolition because of his favourite advocacy which is the Iloilo River Development Project.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2012.
Keywords: Barbecue Park